The disbalance of LRP1 and SIRPα by psychological stress dampens the clearance of tumor cells by macrophages - Yanping Wu; Xiang Luo; Qingqing Zhou; Haibiao Gong; Huaying Gao; Tongzheng Liu; Jiaxu Chen; Lei Liang; Hiroshi Kurihara; Yi-Fang Li; Rong-Rong He (Acta Pharmaceutica Sinica B, 2022)
The relationship between chronic psychological stress and tumorigenesis has been well defined in epidemiological studies; however, the underlying mechanism remains underexplored. In this study, we discovered that impaired macrophage phagocytosis contributed to the psychological stress-evoked tumor susceptibility, and the stress hormone glucocorticoid (GC) was identified as a principal detrimental factor. Mechanistically, GC disturbed the balance of the “eat me” signal receptor (low-density lipoprotein receptor-related protein-1, LRP1) and the “don't eat me” signal receptor (signal regulatory protein alpha, SIRPα). Further analysis revealed that GC led to a direct, glucocorticoid receptor (GR)-dependent trans-repression of LRP1 expression, and the repressed LRP1, in turn, resulted in the elevated gene level of SIRPα by down-regulating miRNA-4695-3p. These data collectively demonstrate that stress induces the imbalance of the LRP1/SIRPα axis and entails the disturbance of tumor cell clearance by macrophages. Our findings provide the mechanistic insight into psychological stress-evoked tumor susceptibility and indicate that the balance of LRP1/SIRPα axis may serve as a potential therapeutic strategy for tumor treatment.